Development of a fixed list of descriptors for the qualitative behavioral assessment of thoroughbred horses in the racing environment - Jaramillo, Fernando Mosquera; Oliveira, Tiago Marcelo; Silva, Pedro Enrique Ayres; Trindade, Pedro Henrique Esteves; Baccarin, Raquel Yvonne Arantes (Frontiers in Veterinary Science, 2023)
Horse racing is a major sport practiced worldwide. The environment to which horses are exposed during race meetings can influence their behavior. However, to the best of our knowledge, a method for assessing a horse's response to its surroundings during the preand post-race periods has not yet been reported. This study aimed to create a standard list of descriptors for use in a qualitative behavioral assessment (QBA) focused on assessing the emotional expressivity of horses before and after racing events. Seventy pre-or postrace 30-second videos of horses were randomly selected from our database of 700 videos.A panel of 8 experienced equine sports medicine specialist veterinarians watched a 60 min presentation on QBA. The panel then watched all videos randomly, simultaneously, individually, continuously, and without any verbal interaction, describing the descriptors related to the emotional expressivity of the horse after each video using a method known as free-choice profiling (FCP). The initial selection of descriptors was based on those indicated by more than one evaluator in the same video, or descriptors with more than 20 occurrences. The second selection was performed based on the content validity index (CVR) to select the descriptors retained in the previous step. Another panel of six veterinarians scored each of the descriptors retained for content validity on a visual scale.Interobserver reliability was estimated using the intraclass correlation coefficient (ICC) and its respective 95% confidence intervals (CI). A natural language processing (NLP) algorithm was used to analyze the behavior (positive or negative polarity) of the descriptors based on the lexicoPT package of R software. NLP analysis considered the descriptors "agitated," "troubled," "restless" and "irritated" to have a negative polarity, while "focused," "relaxed" and "peaceful" had a positive polarity. In the principal component analysis (PCA), descriptors in a negative state were associated with each other and inversely associated with descriptors in a positive state. We conclude with a fixed list of descriptors to be used in a QBA to assess emotional and welfare expressivity in racehorses' preand post-race environments.